Utility of splenic transient elastography in assessing the presence of portal hypertension - A review - Abdulrasak, Mohammed ; 0009-0008-6057-9858; Ahmed, Mustafa; Hootak, Sohail (World journal of methodology, 2025)
Portal hypertension (PH) is a major complication of chronic liver disease, often leading to serious clinical consequences such as variceal bleeding, ascites, and splenomegaly. The current gold standard for PH diagnosis, namely, hepatic venous pressure gradient measurement, is invasive and not widely available. Transient elastography has emerged as a non-invasive alternative for assessing liver stiffness (LS), and recent studies have highlighted the potential role of splenic stiffness (SS) in evaluating PH severity. This narrative review summarizes the available evidence on the utility of splenic transient elastography in assessing PH. We evaluated its diagnostic accuracy, technical challenges, and clinical applications, particularly in distinguishing between cirrhotic PH (CPH) and non-cirrhotic PH (NCPH). A comprehensive literature search was conducted using the PubMed database, focusing on studies that assess splenic elastography in the diagnosis and prognosis of PH. This review compares splenic elastography with other non-invasive imaging modalities, including MR elastography and shear-wave elastography. Additionally, we examined the role of SS using elastography in predicting the presence of esophageal varices and its potential impact on reducing the need for endoscopic screening. Studies have demonstrated that splenic elastography correlates well with PH severity, with cut-off values ranging between 45 kPa and 50 kPa for significant PH detection. Splenic elastography, when combined with platelet count and LS measurements, improves diagnostic accuracy and risk stratification for the occurrence of variceal bleeding. Despite its clinical promise, technical challenges such as patient positioning, body habitus, and probe selection remain key limitations. Notably, splenic elastography may be particularly useful in diagnosing NCPH, where LS remains normal but PH is present. Splenic transient elastography is a valuable adjunct in the non-invasive assessment of PH. Its ability to predict varices, differentiate between CPH and NCPH, and reduce unnecessary endoscopies suggests that it should be incorporated into routine hepatology practice. Future research should focus on refining SS cut-offs, evaluating its cost-effectiveness, and integrating splenic elastography into clinical guidelines for PH management.
©The Author(s) 2025. Published by Baishideng Publishing Group Inc. All rights reserved.